Repeasantization and socio-territorial movements - Rosset, Peter Michael [UNESP]; Ule Muñoz, Cindy Lorena [UNESP] (Taylor & Francis, 2024)
In this essay by two militants of the peasant struggle we put forth repeasantization as a collective action by socio-territorial movements. We review both the external and internal dynamics of depeasantization, brought about by the capitalist system and its agricultural model and the external and internal elements of intentional and systematic collective processes of repeasantization. These are being carried out by peasant families, communities and organizations in their territories, with a special emphasis on the role of organization as critical to success.
Keywords: depeasantization; land; peasantry; Repeasantization; socio-territorial movements; territory